2022
DOI: 10.1002/hyp.14541
|View full text |Cite
|
Sign up to set email alerts
|

Extending the vadose zone: Characterizing the role of snow for liquid water storage and transmission in streamflow generation

Abstract: Streamflow response in headwater catchments is highly sensitive to the hydrologic connectivity of hillslopes to streams during spring snowmelt. Despite strong evidence at point‐ to plot‐scales of flow paths creating lateral connectivity within an alpine snowpack, meltwater is commonly assumed to infiltrate vertically through the snowpack. Hydrologic models only treat the horizontal (downstream) routing of water once released from the snowpack and/or soil column. This assumption limits our ability to represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that increases in average LWC are associated with larger LWC spatial variability and that radar‐based methods for measuring SWE will have increased uncertainty when LWC is present in the snowpack (Bonnell et al, 2021; Webb et al, 2022). Although we do not estimate LWC, we identify a large shift between dry and wet relative permittivity sills (Table S5), indicating that relative permittivity variance is higher for wet snow surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that increases in average LWC are associated with larger LWC spatial variability and that radar‐based methods for measuring SWE will have increased uncertainty when LWC is present in the snowpack (Bonnell et al, 2021; Webb et al, 2022). Although we do not estimate LWC, we identify a large shift between dry and wet relative permittivity sills (Table S5), indicating that relative permittivity variance is higher for wet snow surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2021) Approximately 1/4 of the watersheds studied receive >30% of annual precipitation as snow, which is not accounted for in the hydrologic signatures as implemented here, yet snowmelt as an antecedent moisture source can impact streamflow response at the event scale (Hammond & Kampf, 2020). Burned areas show impacts to snow accumulation and accelerated snowmelt after wildfire (Gleason et al, 2019;Kampf et al, 2022) and snowmelt can generate both saturation and IE as flowpaths converge within the snowpack (Webb et al, 2022). The missing representation of snowmelt could explain some of the variability in our signature values.…”
Section: Timescales Of Recovery From Wildfire Impacts On Overland Flo...mentioning
confidence: 99%